Capability of Pocket Penetrometer to Evaluate Unconfined Compressive Strength of Baghdad Clayey Soil - Yasun, Azhar Sadiq (Al-Nahrain Journal for Engineering Sciences, 2018)
Unconfined compressive strength represents an important parameter for soil investigation report test results because the values of cohesion and allowable bearing capacity can directly obtained from the relevant test especially if the clayey soil layers are found at sufficient enough depth above water table level._x000D_ This paper deals with simple comparison (based on (31) soil samples) between unconfined compressive strength (qu) obtained by using the pocket soil penetrometer tool and the unconfined compressive strength using the conventional test for the same sample penetrated by the pocket penetrometer with different soil moisture contents. Two triaxial specimens, sample type-1- with dimensions 38 X 79mm and type-2- with dimensions 33 X 79mm(diam. X height)) prepared in the libratory._x000D_ It was found that the results refers that soil pocket penetrometer readings are closed enough to the results that obtained from the unconfined compression test result with certain conditions._x000D_ The average percentage of difference between penetrometer readings and unconfined compression test result values was (1.103%) for sample type-1- and (1.53%) for sample type -2-._x000D_ The maximum moisture content for all tests samples was (27.3%) and the minimum was (14.7%) while the average moisture content was(20.9%).